Special Issue: Past and Future Trends and Variability in Hydro-Climatic Processes - Barrie R. Bonsal; Yonas B. Dibike; Daniel L. Peters; Rajesh R. Shrestha (Water, 2021)
The earth has vast amounts of surface and sub-surface freshwater in the form of lakes, reservoirs, rivers, wetlands, soil water, groundwater, as well as water stored in snowpacks, glaciers, and permafrost [.]